Structural and Spectroscopic Study of Novel Tetradentate Macrocyclic Ligand Type N4 and It’s Complexes with CrIII, MnII, FeII, CoII, NiII ,CuII, PdII and CdII - Al-Jeboori, M.J.; Lateef, S.M.; Mohammed, A. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Ethylenediamine was reacted in the first step with 2,5 â€“ hexandion to produce the precursor [A] , then [A] was reacted with diethylmalonate to give the new tetradentate macrocyclic Ligand [H2L].This Ligand was reacted with some metal ions in ethanol to give a series of new metal complexes of the general formula [M(HnL)X]m  ( where : M= CrIII  ,      n = 0 ,  X= Cl2 , m= -1 ;  M = MnII , FeII , NiII , CuII ,      n = 1 , X= Cl2 , m = -1 ;  M = CoII , n = 0 ,       X = Cl , m = -1 ; M = PdII , n = 0 , X=0 , m = 0  ; M = CdII , n = 2 , X = 0 ,     m = +2 .  All compounds were characterized by spectroscopic methods [I.R, U.V-Vis , HPLC , Atomic Absorption] , microanalysis of elements (C.H.N) along with conductivity measurements . From the above date the proposed molecular structure for CrIII , MnII , FeII , NiII and CuII  complexes is octahedral, While CoII , PdII, and CdII form trigonal bipyramid , square planar and tetrahedral geometries respectively .